Nanocarrier spray: a nontransgenic approach for crop engineering. (March 2023) - Kandhol, Nidhi; Singh, Vijay Pratap; Herrera-Estrella, Luis; Tran, Lam-Son Phan; Tripathi, Durgesh Kumar
Abstract: Genetic modification allows engineering of important traits in crops through expensive and tedious procedures to alter their genetic background. Recently, Thagun et al. developed a nanocarrier-based foliar spray method to translocate bioactive molecules of interest into plant cells to engineer important traits without introducing a transgene.